Pembelajaran Gramatikal Bahasa Arab Menggunakan Metode Al Miftah Lil Ulum - Zaeni, Akhmad; Hasanah, Wildatuz Zuhro (An-Nuqthah, 2024)
The application of the Al Miftah Lil Ulum method facilitates the understanding of grammatical lessons, particularly Nahwu and Sharaf, for students at MADIN Miftahul Ulum. This method is designed to address the difficulties students face in comprehending grammatical lessons, which are often considered complex and tedious. Al Miftah Lil Ulum simplifies material from classical texts such as Jurumiyah, Alfiyah, and Al-‘Imriti with a more concise, easily understandable approach, tailored to the students' needs, including the use of Indonesian, tables, and children's songs. This study utilizes observation and documentation to collect data, aiming to expand access to grammatical understanding and increase students' interest in learning Arabic. The results show that this method successfully facilitates students' comprehension of grammatical knowledge and enhances their ability to read traditional Islamic texts, making it an effective solution in the teaching of grammar in Islamic schools and madrasahs